Design and Development of a Web-based Online Store Application for Yudistira Jaya Stationery Shop - Muhammad Abdul Aziz Abyan; Untung Surapati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
The accelerated progress of information technology has fundamentally reshaped the landscape of the trade sector, with notable impacts on micro, small, and medium enterprises (MSMEs). This research aims to design and develop a web-based online sales platform tailored for ATK Yudistira Jaya, a stationery and photocopy service provider, to optimize operational efficiency and broaden market accessibility. The development process employs the Waterfall methodology, a systematic approach that ensures structured progression through distinct phases of system creation. The technological foundation of the platform is built using the Laravel framework for backend operations, paired with MySQL as the database management system to handle data storage and retrieval effectively. Findings from the system evaluation indicate that the developed platform adequately addresses the functional requirements of both administrators and end-users. Key features integrated into the system include a comprehensive product catalog for easy browsing, a streamlined order placement mechanism, secure payment integration through a trusted gateway, and robust order management tools to track and process transactions. The successful implementation of this digital solution is anticipated to empower MSMEs like ATK Yudistira Jaya by equipping them with the necessary tools to navigate the challenges of a digital marketplace, ultimately enhancing their competitive edge through strategic adoption of technology.